Evaluation of programs, services and technologies from the health promotion perspective: a theoretical reflection - Ana Lúcia Mendes Lopes; Simone Albino da Silva; Danielle Freitas Alvim de Castro; Cláudia Maria Bógus; Lislaine Aparecida Fracolli (Universidade de Fortaleza, 2014)
Objective: To perform a theoretical reflection concerning the use of the 'evaluation' concepts, for application in health promotion's technologies, programs and services. Data Synthesis: With a brief description of health assessment and health promotion conceptual aspects, stands out the importance of adopting evaluative models that address the complexity and multiplicity of practices. It is hence expected to expand the limits of the biomedical sciences and traditional epidemiology, also underpinned by the social sciences and humanities. Following these considerations, it is proposed that evaluations have as principles: being participative; being introduced at the beginning of the program/technology/service and taking part in all stages of its development; encompassing strategies for sharing the findings with all actors involved. Is suggested the triangulation of qualitative and quantitative methods and scientific techniques, with capacity to embrace the subject complexity, such as document analysis, individual interviews, focus groups, survey of primary or secondary data in databases, direct or participative observations. Conclusion: The reflection proposed indicated that emphasis on learning, action and transformation of social practices should compose the guidelines of health promotion evaluative models. The knowledge produced has the potential to strengthen the practice of health promotion, the intersectionality, social mobilization, partnerships, sustainability and the advocacy of public health. doi:http://dx.doi.org/10.5020/18061230.2013.p590